Spatiotemporal dynamics and driving mechanisms of coupled coordination between rural–urban integration and rural resilience in Southwest China - Zhengyong Yu; Jiqing Lin; Yifei Zhao; Wei Liu (Scientific Reports)
Abstract The coordinated development of urban–rural integration and rural resilience is of great significance for the achievement of regional sustainable development and the United Nations Sustainable Development Goals. This study explores the coupled and coordinated evolution between ur-ban-rural integration and rural resilience and its driving mechanism in Southwest China. By constructing an evaluation index system for urban–rural integration development and rural resilience, this research analyses the spatial and temporal evolution characteristics and influencing factors of urban–rural integration and rural resilience in Southwest China from 2012 to 2022 by applying the entropy weighting method, comprehensive evaluation model, coordination degree model, and geodetector model. The results show that the overall coupled coordination degree of urban–rural integration and rural resilience in Southwest China shows an upward trend, but there are significant spatial differences among provinces, with higher coupled coordination degrees in Yunnan and Sichuan and lower ones in Tibet and Guizhou. The analysis of the temporal evolution of the degree of coupling coordination reveals a trend of gradually increasing regional coordination, while the analysis of the spatial evolution shows a spatial pattern of high in the centre and low on both sides. In addition, the level of infrastructure, economic development, and resource endowment are the main factors affecting the degree of coordination between urban–rural integration and rural resilience. The findings of this study provide a decision-making reference for policy makers, pointing out key areas such as strengthening infrastructure development, promoting balanced regional economic development, and rationally utilizing resource endowments to promote the coordinated development of urban–rural integration and rural resilience in the Southwest region and to realize sustainable regional development.